Developing a profile of religions in Malaysia for inter-faith discourses - Ibrahim, Haslina (2011)
Malaysians need more than historical explanation to substantiate the reasons for their coexistence and understanding of each other. This paper is to share part of our research endeavor in gathering and managing data on religions in Malaysia through an academic research. Using a combination of approaches; we try to go beyond the phenomenological approach in developing a profile of religions in Malaysia. We have identified two major categories as the criteria for the profile; the permanent and the dynamic. The permanent pertains to; God as the Creator, the universe and creation, the relationship between the creator and the creation, the concept of good and evil and the destiny of the universe. The dynamic pertains to the philosophy, concept, notion, and methods and approaches for understanding the permanent. This paper therefore advocates the profile as potential standard for embarking into inter-faith discourses among religions in Malaysia.